2020
DOI: 10.1098/rsos.200570
|View full text |Cite
|
Sign up to set email alerts
|

Postural stability in human running with step-down perturbations: an experimental and numerical study

Abstract: Postural stability is one of the most crucial elements in bipedal locomotion. Bipeds are dynamically unstable and need to maintain their trunk upright against the rotations induced by the ground reaction forces (GRFs), especially when running. Gait studies report that the GRF vectors focus around a virtual point above the centre of mass (VP A ), while the trunk moves forward in pitch axis during the stance phase of human running. However, a recent simulation study suggests that a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…In addition, an increasing dispersion between the participants with increasing perturbation of upright gait can also be observed in other studies, e.g. walking down visible and camouflaged curbs [12] or running down camouflaged drops [20].…”
Section: Virtual Pivot Point In Lola-like Walkingsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, an increasing dispersion between the participants with increasing perturbation of upright gait can also be observed in other studies, e.g. walking down visible and camouflaged curbs [12] or running down camouflaged drops [20].…”
Section: Virtual Pivot Point In Lola-like Walkingsupporting
confidence: 76%
“…In those experiments, the GRFs point to the VPP with a small spread. In simulations of running humans, humanoid robots and birds, there were stable solutions for the VPP position both below and above the CoM [18][19][20][21]. However, the question arises whether the VPP is a target driving the gait strategy or merely a consequence of the complex dynamics and control during gait.…”
Section: Introductionmentioning
confidence: 99%
“…The VPP template can perhaps be understood as a global representation of coupled contralateral central pattern generators (CPGs) (Brown, 1914; Grillner and Manira, 2020; Grillner and Zangger, 1979). Simulation studies showed that stable bipedal gaits emerge for certain values of VPP position in body frame and leg impedance (Andrada et al, 2014; Drama et al, 2020; Maus et al, 2010). Note that these parameters were adapted by our analyzed dogs when changing from walk to trot (see e.g., Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, if the VPP is placed caudally to the proximal pivot, as depicted in dogs' thoracic limb, the torque generated will absorb energy. In this case the leg must add energy axially to the system for the sake of periodicity (Blickhan et al, 2015;Drama and Badri-Spröwitz, 2020). Accordingly, the dogs under study here, except Whippets during walk, add energy axially to the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation